Barriers to healthcare workers reporting adverse events following immunization in Zhejiang province, China. Issue 5 (30th November 2022) - Lv, Huakun; Pan, Xuejiao; Wang, Ying; Liang, Hui; Yu, Hu
ABSTRACT: Objectives: A cross-sectional survey was conducted among healthcare workers (HCWs) to assess their knowledge, attitude, and reporting behavior in adverse event following immunization (AEFI) surveillance as well as to identify barriers. Methods: A simple random sample of 170 vaccination clinics was selected and one HCW was informed to participate in this survey in each selected vaccination clinic. The survey was developed using a secure online platform and consisted of a structured online questionnaire. The distributions of the respondents' characteristics were presented. Training status, knowledge, attitude, and reporting behavior were compared between sub-groups of HCWs. Barriers and suggestions on AEFI reporting were also summarized. Results: Of the 170 surveyed HCWs, 61.76% received the training on AEFI surveillance while 15.88% had no AEFI training at all. The higher level of knowledge and the more positive attitude and reporting behavior on AEFI surveillance were observed among HCWs with the longer working duration on AEFI surveillance, or among HCWs who received the training. The most critical barrier to reporting an AEFI was 'not being sure if the AEFI is related to the vaccine' (122, 71.76%). Other barriers were: 'I do not want to raise unnecessary public alarm about a vaccine' (105, 61.76%); 'reporting form or other method being too complicated' (65, 38.23%). Conclusion: The study findings highlighted the need to prioritize training on AEFI surveillance for HCWs. It is recommended that the development of the targeted interventions to strengthen AEFI surveillance system be required based on the barriers found in this study.